Geometry Dependence of the Magnetization Reversal Process in Bridged Dots - Altbir-Drullinsky, D; Escobar-Donoso, R (Elsevier B.V., 2017)
Based on Monte Carlo numerical simulations: results for the magnetization reversal process in thin circular Ni dots connected by a bridge are presented. The dependence of the process on both the width of the bridge and the orientation of the applied magnetic field has been investigated. It was found that when the applied magnetic field is set parallel to the bridge, the hysteresis curves are weakly dependent on the width of the bridge, being rather close to that of a single dot of the same diameter. On the other hand, when the magnetic field is applied perpendicularly to the bridge, a significant reduction in the coercivity of the system is obtained, even in the case of narrower bridges. © 2017 Elsevier B.V.